Glucocorticoid Minimization in Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis: An International Survey of Clinicians - David Massicotte-Azarniouch; Mark Canney; Priscilla Karnabi; Peter A. Merkel; Rachel B. Jones; Ruth J. Pepper; Alan D. Salama; Vimal K. Derebail; Nataliya Milman; Mats Junek; Christian Pagnoux; David R.W. Jayne; et al. (Kidney Medicine, 2024)
Rationale & Objective: Research in anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV) has focused on reducing treatment toxicities, notably through reduction of exposure to glucocorticoids. Glucocorticoid-sparing therapies such as avacopan are not widely available in many countries, and patients are exposed to high glucocorticoid doses. There is little data concerning what clinicians should accept as the lowest glucocorticoid dosing that can be used in induction therapy for AAV. Study Design: International, online survey. Setting & Participants: Clinicians in various countries with experience in managing vasculitis. Exposure and Outcomes: Survey questions to gauge interest and preferences in studying an induction of remission regimen for severe AAV using only 2 or 4 weeks of glucocorticoids without avacopan. Data collected included general opinions about standard of care for induction agents, glucocorticoids, and avacopan. Respondents were presented with 3 candidate trial designs, 2 of which proposed a combination of cyclophosphamide and rituximab induction. Analytical Approach: Using a 10-point Likert scale, respondents ranked each candidate trial on its usefulness in demonstrating whether a minimal glucocorticoid regimen would be safe and effective and their willingness to randomize into the trial. Results: There were 210 respondents to the survey. The candidate trials were rated moderate-to-high for usefulness to demonstrate safety and efficacy (scores 6-7/10), and moderate (scores 5-6/10) for willingness to randomize. Four-week glucocorticoid duration was preferred to 2 weeks, and combination cyclophosphamide-rituximab with 4-week glucocorticoids was the most preferred design. Forty-two percent of respondents felt avacopan had to be incorporated into a minimal GC trial design to want to recruit patients. Limitations: Representativeness of survey sample and generalizability of findings. Conclusions: Combination cyclophosphamide-rituximab may be the ideal way of studying minimal glucocorticoid use in severe AAV. Given its increasing uptake, incorporating avacopan into a potential trial design is important. Plain Language Summary: Research in anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV) has focused on using less glucocorticoids to limit side effects. New drugs that drastically limit glucocorticoid use are not available in many countries. Studies are needed to find other ways of reducing glucocorticoid exposure to treat AAV, but it is unclear how best to achieve this. We administered a survey to doctors with experience in treating AAV and had them grade different combinations of widely available treatments with 2 or 4 weeks of glucocorticoids. We found that a combination of 2 doses cyclophosphamide with 2 doses rituximab and 4 weeks of glucocorticoids was the preferred treatment. The results will guide the development of a trial studying minimal use of glucocorticoids for the treatment of AAV.